2009
DOI: 10.1177/001979390906200205
|View full text |Cite
|
Sign up to set email alerts
|

Do Changes in Regulation Affect Employment Duration in Temporary Help Agencies?

Abstract: The employment duration of workers in temporary help agencies is seen as an important indicator of their job quality. Most of the countries that regulate temporary agency employment do so to ensure at least a minimal level of employment stability. Over the past three decades Germany has repeatedly liberalized the law on temporary agency employment. These successive reforms should have affected the employment duration in the temporary employment sector. Applying a mixed proportional hazard rate model to adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
87
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 32 publications
3
87
1
1
Order By: Relevance
“…One reason why flexibility is not often mentioned could be that flexibility, that is, with regard to part-time work arrangements as they are known (e.g. from the UK and the Netherlands) are rare in Germany, where the usual contract is on a full-time basis (Antoni & Jahn, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…One reason why flexibility is not often mentioned could be that flexibility, that is, with regard to part-time work arrangements as they are known (e.g. from the UK and the Netherlands) are rare in Germany, where the usual contract is on a full-time basis (Antoni & Jahn, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Third, unemployed job-seekers often try to escape unemployment by upgrading their education, but do temp work at the same time to augment their income. Since their motivation might not be primarily to find employment outside the 6 For Germany, Antoni and Jahn (2009) provide evidence that permanent agency staff members account for about 7 percent of the stock of all workers identified as temp workers via the industry classification code. In the inflow to temp jobs from unemployment, this ratio is likely to be considerably lower, since the staff of temp agencies obviously experience fewer transitions into and out of jobs than the temp workers themselves.…”
mentioning
confidence: 99%
“…2 The growing importance of TAW is inspiring a large and growing literature on the different aspects of temporary agency work. Inter alia, several studies show that there is a significant wage gap between TAW and regular employees, albeit varying in size (Jahn, 2010;Antoni & Jahn, 2009;Oberst, et al, 2008;Houseman, et al, 2003;Jahn & Rudolph, 2002). This points to potential cost savings for firms, often seen as the main incentive to use TAW (Bryson, 2013;Heywood, et al, 2011;Kleinknecht, et al, 2006;Houseman, et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For more information see Zühlke et al (2004) It is often observed that TAW earn less than their colleagues with open-end contracts (Jahn, 2010;Antoni & Jahn, 2009;Houseman, et al, 2003;Jahn & Rudolph, 2002). However, this does not necessarily mean that the costs for the customer firms are lower when they use TAW instead of permanent employees.…”
mentioning
confidence: 99%
See 1 more Smart Citation